Dynamic analysis of platelet deposition to resolve platelet adhesion receptor activity in whole blood at arterial shear rate. (27th March 2014) - Pugh, Nicholas; Bihan, Dominique; Perry, David J.; Farndale, Richard W.
Abstract: Platelet activation is traditionally quantified using turbidimetric aggregometry, which reflects integrin αIIb β3 activity, an important determinant of platelet function during pathophysiological thrombus formation. However, aggregometry does not recreate the shear conditions prevailing during thrombosis in vivo . Here we describe novel whole-frame analysis of real-time video microscopy to quantify platelet adhesion receptor activity under shear in parallel-plate flow chambers. We demonstrate that the rate of change of surface coverage (designated Platelet Population Mobility, PM ) quantifies platelet mobility. On collagen, PM falls exponentially to a low level, corresponding to firm platelet adhesion, while on other substrates, PM remains high. Different receptor-specific thrombogenic surfaces reveal that the PM time constant reflects real-time changes in integrins αIIb β3 and α2 β1 activity. This ensemble kinetic analysis has the potential to provide valuable diagnostic information about platelet thrombus formation with both academic and clinical applications.